2021
DOI: 10.1155/2021/1783485
|View full text |Cite
|
Sign up to set email alerts
|

Bavachin Induces Ferroptosis through the STAT3/P53/SLC7A11 Axis in Osteosarcoma Cells

Abstract: Ferroptosis is a new form of regulated cell death, which is mediated by intracellular iron. Although it is reported that bavachin has antitumour effects on several tumour cells and prompts the reactive oxygen species (ROS) generation, it is unclear whether ferroptosis can be induced by bavachin in osteosarcoma (OS) cells. In this study, we found that bavachin inhibits the viability of MG63 and HOS OS cell lines along with an increase in the ferrous iron level, ROS accumulation, malondialdehyde overexpression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 50 publications
7
59
0
Order By: Relevance
“…As displayed in Figure 3C , the expression of SLC7A11 in the Nano-PEG@CeO 2 group was significantly downregulated, in comparison with the control group. It was reflected that Nano-PEG@CeO 2 could regulate ferroptosis of tumor cells, as similarly reported before ( Hong et al, 2021 ; Luo et al, 2021b ). Furthermore, the expression of p53 with Nano-PMI@CeO 2 treatment was remarkably increased compared with the control group.…”
Section: Resultssupporting
confidence: 80%
“…As displayed in Figure 3C , the expression of SLC7A11 in the Nano-PEG@CeO 2 group was significantly downregulated, in comparison with the control group. It was reflected that Nano-PEG@CeO 2 could regulate ferroptosis of tumor cells, as similarly reported before ( Hong et al, 2021 ; Luo et al, 2021b ). Furthermore, the expression of p53 with Nano-PMI@CeO 2 treatment was remarkably increased compared with the control group.…”
Section: Resultssupporting
confidence: 80%
“…SLC7A11 and GPX4 may be the most valuable pharmacological targets in the ferroptosis network. This has been confirmed by several studies on traditional antitumors drugs such as olaparib ( Hong et al, 2021 ), tanshinone IIA ( Guan et al, 2020 ) and bavachin ( Luo et al, 2021 ). The poly (ADP-ribose) polymerase olaparib has been demonstrated to promote ferroptosis in ovarian cancer cells by downregulating SLC7A11 expression ( Hong et al, 2021 ).…”
Section: Effects Of P53 Ptms On Ferroptosismentioning
confidence: 54%
“…Tanshinone IIA, the active ingredient of Chinese herbal medicine Salvia miltiorrhiza Bunge, also promotes ferroptosis in gastric cancer cells via p53/SLC7A11 ( Guan et al, 2020 ). Bavachin induces ferroptosis in osteosarcoma cells via repressing SLC7A11 ( Luo et al, 2021 ). Interestingly, bavachin also increases intracellular labile iron levels ( Luo et al, 2021 ).…”
Section: Effects Of P53 Ptms On Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggested that STAT3 is a risk gene in gliomas, consistent with the results of the present study 36 . Hu et al found that bavachin could induce ferroptosis through the STAT3/P53/SLC7A11 Axis 37 . Furthermore, CA9 was shown to be highly overexpressed in GBM, conferring radiation resistance in glioma cells 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%